Biophysical characterization of the structure of a SARS-CoV-2 self-amplifying RNA (saRNA) vaccine. Issue 1 (14th February 2023) - Myatt, Daniel P; Wharram, Lewis; Graham, Charlotte; Liddell, John; Branton, Harvey; Pizzey, Claire; Cowieson, Nathan; Rambo, Robert; Shattock, Robin J
Abstract: The current SARS-Covid-2 (SARS-CoV-2) pandemic has led to an acceleration of messenger ribonucleic acid (mRNA) vaccine technology. The development of production processes for these large mRNA molecules, especially self-amplifying mRNA (saRNA), has required concomitant development of analytical characterization techniques. Characterizing the purity, shape and structure of these biomolecules is key to their successful performance as drug products. This article describes the biophysical characterization of the Imperial College London Self-amplifying viral RNA vaccine (IMP-1) developed for SARS-CoV-2. A variety of analytical techniques have been used to characterize the IMP-1 RNA molecule. In this article, we use ultraviolet spectroscopy, dynamic light scattering, size-exclusion chromatography small-angle X-ray scattering and circular dichroism to determine key biophysical attributes of IMP-1. Each technique provides important information about the concentration, size, shape, structure and purity of the molecule.